Selecting Directions for Parallel RAMS Performance Optimization - Mendes, Celso L.; Panetta, Jairo (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 1999: Anais do XI Symposium on Computer Architecture and High Performance Computing, 1999)
This paper presents the results from a preliminary performance evaluation of parallel RAMS, a numerical weather prediction model designed to simulate atmospheric phenomena at a regional level. The main goal in our work was to study in detail the performance of the current RAMS version, and to uncover aspects of its code where opportunities for optimization exist. We present our observations on both computation and communication performance of RAMS executing on a distributed memory parallel platform, and analyze their contributions to total program performance. From the observed data, we present simulations that predict bounds on potential performance gains for possible load balancing strategies.